The Debates of the Createdness of the Qur’an and its Impact to the Methodology of Qur’anic Interpretation - Safrudin Ediwibowo (Universitas Islam Negeri Mataram, 2015)
The status of the Qur'an as the verbatim words of God has become undisputed belief among Muslims. However, beyond the agreement on this fundamental doctrine, they differed from interpreting the nature of